Does Health Insurance Ownership Determine Access and Frequency of Hospitalization? Evidence from the Two-part Poisson Model - Samsudin, Shamzaeffa; Abu-Bakar, Arpah; Regupathi, Angappan; Aljunid, Syed Mohamed (International Journal of Economics and Financial Issues, 2016)
This paper examined the effect of health insurance ownership on hospitalization within the context of Malaysia. The study utilized the data from Malaysia National Health and Morbidity Survey III (2006) and 14,234 respondents were selected for this purpose. Malaysia provides new evidence from an emerging market where voluntary purchase of private health insurance co-exists with almost free public health care. We used the standard and two-part Poisson models in determining the effect of insurance ownership on utilization. Based on two selection criteria, two-part Poisson model was found to be superior to the standard specification. Insurance ownership was found to be significant in determining access while it has no significant effect on frequency of hospitalization. Other significant variables that determine access were age, marital status, household size, health status and income while health status is the sole factor that affects frequency. Keywords: health insurance, hospital utilization, Poisson model JEL Classification: I13